Coordination of steer angles, tyre inflation pressure, brake and drive torques for vehicle dynamics control - Shyrokau, Barys (2015)
During vehicle operation, the control objectives of stability, handling, energy consumption and comfort have different priorities, which are determined by road conditions and driver behavior. To achieve better operation characteristics of vehicle, coordinated control of vehicle subsystems is actively used. The fact of more active vehicle subsystems in a modern passenger car provides more flexibility for vehicle control and control algorithm development. Since the modern vehicle can be considered as over-actuated system, control allocation is an effective control technique to solve such kind of problem.